Experimental study of heat transfer coefficient of nanofluid flow through a plain tube - Azrul Azam, Nizarudin (2010)
Heat transfer is one of the most important processes in many industrial. The inherently poor thermal performance of common fluids put a limitation and restricted in developing energy efficient heat transfer fluid. With a strong needed by industry in developing energy efficient, advance heat transfer fluid called nanofluid is introduced. Nanofluid is prepared by two step technique in this study by diluting Alumina nanoparticles with water at three different concentrations 0.02%, 0.10% and 0.50%. The heat transfer coefficient was investigated experimentally in a flow loop with a horizontal tube test section subjected to constant heat flux at a various flow rate ranges between Reynolds number 4,000 to 20,000. Initial experiments were conducted with pure water for experiment validation and accuracy. The experimental results, represented in Nusselt number (Nu) are compared to classical Gnielinski equation and Dittus-Boelter equation and observed that both equations are applicable in turbulent flow range for single phase fluid with considerable deviation was observed. Addition of the nanoparticles to the base fluid significantly increased their heat transfer coefficient and the maximum enhancement of 19.80% compared with pure water with 0.50%volume concentration and at Reynolds number 8,400 was observed in this study. However, increasing of small amount of volume concentrations in the small range studied in this work did not show much effect on heat transfer enhancement. Experimental result were compared with previous result in literature and numerical study and found consistent with considerable deviation observed.